A study on the library services and facilities provided to physically handicapped in Quezon City Public Library System - Dacca, Princess O. (2008)
This study aimed to determine the present condition of the library services and facilities of the Quezon City Public Library System for the physically handicapped users. It aimed to propose and develop possible recommendations for the improvement of the library services and facilities geared towards the satisfaction of physically handicapped library patrons.